Fossil woods from the permian and triassic of Mozambique: taxonomy, palaeocology and geoconservation - Nhamutole, Nelson Ernesto (My University, 2021)
Despite the discovery of immense fossil forests in Mozambique over 150 years ago, meager palaeontological research has been directed to this unique legacy of Earth’s history. As a consequence, only one outdated genus was known to date in Mozambique. To change this scenario, fossil woods from Permian and Triassic formations from the Tete and Niassa Provinces, Centre and Northern of Mozambique, were collected during three consecutive field campaigns in 2017, 2018 and 2019. Over 300 samples were sectioned and studied microscopically. As a result, important insights on the taxonomy, palaeoecology, palaeoclimates and geoconservation are provided and improve significantly our knowledge on one of the largest fossil forests in the world. Taxonomically, six genera and seven species are now identified, consisting of Agathoxylon africanum, Agathoxylon karooensis, Australoxylon teixeirae, Prototaxoxylon uniseriale, Taxodioxylon sp., Cupressinoxylon sp. nov, Protaxodioxylon sp. nov. 1 and Protaxodioxylon sp. nov. 2. The latter three taxa are assigned to new species but only the latter two have been submitted for publication. Agathoxylon africanum and Australoxylon teixeirae seem to be endemic to Gondwana, sustaining the idea of species-level provincialism based on Glossopteris leaf fossils. With the addition of the Mozambican occurrence, Australoxylon teixeirae represents the most widespread taxon in Gondwana. Based on growth ring analysis, it is found that the trees sampled show well-marked, wide, growth rings suggesting well-defined seasons. Most of the woods studied present rings belonging to D-type and S-type. S-type growth rings indicate extreme conditions dominated by very wet and hot climate with the possible occurrence of disease or post-depositional compression. Four fossil forests were also analyzed qualitatively and quantitatively. These forests, subdivided into Nhambando, Mapembera, Cadzewe and Carangache, are interesting for geotourism. In Mozambique, however, more straightforward decisions are needed to ensure the full legal protection of such sites and the implementation of safe geotourism. Although the number of specimens with good preservation is relatively low, this study represents an important contribution to fill gaps in the understanding of the Gondwana palaeoflora in the Southern Hemisphere as a whole
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2021